Treatment of skin cancer arising within a burn scar (case report) - I. V. Fedorkevich; T. N. Nesterovich; O. N. Ganusevich; S. A. Ivanov; S. L. Achinovich; D. M. Los (Сибирский онкологический журнал, 2022)
Background. In 1–2 % of cases, burn scars can cause more aggressive skin cancer that has a worse prognosis than conventional skin cancer. Most burn scar carcinomas are the squamous cell type (88 %) with the frequency of metastasis of 27 %. Due to the rarity of this malignancy and absence of guidance, treatment of scar carcinoma continues to be controversial. Surgical excision remains a standard mode of treatment for squamous cell carcinoma of the skin. Surgery is associated with problems to define a required limit to achieve clear margins; and subsequent grafting of the postoperative defect is limited due to the rigidity of the surrounding tissue and microcirculatory defects.Case description. We present a case report of squamous cell carcinoma of the skin originating from burn scars. The patient received a radical course of conformal external beam therapy with a total dose of of 68 Gy in 2 Gy single doses (34 fractions) resulting in an increase in the ulcer due to the destruction of the infiltrative component of the tumor. Radical electrosurgical excision of the tumor with a free TRAM-flap reconstruction in the MS-0 version (using the full width of the rectus abdominis muscle) was performed. Microvascular anastomoses were made between the deep lower epigastric and thoracodorsal vessels on the right. There were no postoperative complications. No evidence of recurrence and tumor progression was found with a follow-up for 7 months.Conclusion. A personified approach to the treatment of burn scar carcinoma demonstrated good treatment outcomes. Surgical reconstruction of the postoperative defect in these patients may require the use of composite flaps and, in specific cases, microsurgical techniques.